2017
DOI: 10.1016/j.jchf.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Metabolomic Profiling of Plasma and Survival in Heart Failure Patients

Abstract: Background Profiling of plasma metabolites to predict the course of heart failure (HF) appears promising but validation and incremental value are less established. Methods Patients meeting Framingham HF criteria with history of reduced ejection fraction were (n=1032) were randomly divided into derivation and validation cohorts (n=516 each). Amino acids, organic acids, and acylcarnitines were quantified using mass spectrometry in fasting plasma samples. We derived a prognostic metabolite profile (PMP) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 38 publications
4
84
1
1
Order By: Relevance
“…5À9 However, data regarding metabolomics in nonischemic DCM are scarce, 10 whereas the metabolic profile is likely to be different from that of ischemic HF. 9 Modeling of large biologic data sets represents a unique opportunity to predict disease severity better, as compared to single biomarkers. However, statistical classification is a critical component of utilizing metabolomics data for examining the phenotypical determinants.…”
Section: Introductionmentioning
confidence: 99%
“…5À9 However, data regarding metabolomics in nonischemic DCM are scarce, 10 whereas the metabolic profile is likely to be different from that of ischemic HF. 9 Modeling of large biologic data sets represents a unique opportunity to predict disease severity better, as compared to single biomarkers. However, statistical classification is a critical component of utilizing metabolomics data for examining the phenotypical determinants.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolome encompasses a large variety of metabolites, the small intermediary molecules in metabolism. Metabolomics has been increasingly used to investigate metabolic pathways in cardiovascular diseases [23][24][25][26][27], including mitral valve disease in both dogs [9] and humans [15]. Emerging evidence points to derangements in cardiac metabolism including perturbations in mitochondrial bioenergetics and reactive oxygen species (ROS) homeostasis in failing hearts [1].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lanfear et al identified and then validated a panel of 13 circulating metabolites as a predictor of mortality risk in HF patients after accounting for conventional clinical risk factors and NT-proBNP levels. 28 Another prospective population-based study deriving a risk score from four metabolites and validating this score in two cohorts found improved risk reclassification of CHF patients using the biomarker score, although discrimination was not significantly enhanced. 29 A meta-analysis of 18 metabolomic prediction studies of CV disease outcomes reported an average change in c-statistic of 0.0417 (standard error 0.008) after adding metabolite-based information, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%